Glutamate: The Master Neurotransmitter and Its Implications in Chronic Stress and Mood Disorders - Pal, Mia Michaela (Frontiers in Human Neuroscience, 2021)
This brief review article makes the argument that glutamate is deserving of its newfound attention within the neuroscience literature and that many directions of important research have yet to be explored. Glutamate is an excitatory neurotransmitter with several types of receptors found throughout the central nervous system, and its metabolism is important to maintaining optimal levels within the extracellular space. As such, it is important to memory, cognition, and mood regulation. The mechanisms by which chronic stress affect the glutamatergic system and neuroplasticity are outlined. Several implications for potential pharmacologic and nonpharmacologic interventions are discussed.